Open feed organic heater pressure analysis on single-stage regenerative organic Rankine cycle performance - Ghalya Pikra; Nur Rohmah; Rakhmad Indra Pramana; Andri Joko Purwanto (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2020)
Single-stage regenerative organic Rankine cycle (SSRORC) is a system that is used for increasing the simple organic Rankine cycle (ORC) performance. Open feed organic heater (OFOH) addition in the ORC system increase power and efficiency of the system. This paper analyzes the SSRORC performance with a variation of P6/P1 ranges from 1.25 to 3.75 with an increment of 0.25, where P6 is the OFOH pressure at the inlet side and P1 is the pressure at the inlet pump 1, respectively. Hot water was used as the heat source with 100 °C and 100 l/min of temperature and volume flow rate as the initial data. R227ea, R245fa, and R141b were chosen as working fluids for performance analysis. The analysis was performed by calculating the heat input, heat loss, pump and turbine power, net power, and thermal efficiency through energy balance. Exergy input, exergy output, and exergy efficiency were analyzed through exergy balance. The results show that P6/P1 = 2 obtains the highest performance than the other pressure ratios for R227ea, while R245fa and R141b obtain the highest performance at P6/P1 = 2.25. R141b has better performance than the other two fluids with 10.97 % and 11.96 % for thermal and exergy efficiency. The results show that the ratio of OFOH pressure at the inlet side to the pressure at inlet pump 1 (P6/P1) in the middle value obtains the best performance.